Low-temperature-resistant graphene fiber energy storage device and preparation method thereof
By growing nano silver iodide on the surface of graphene fiber electrodes and grafting solid electrolyte nano silver iodide in situ by using Co60-ray irradiation, the problems of energy storage characteristics and electrochemical performance of graphene capacitors in low temperature environments are solved, and efficient improvement of low-temperature electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411927834.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
Existing graphene capacitors cannot maintain high energy storage characteristics and fast charging and discharging capabilities in low temperature environments below -40°C, and the ion transfer kinetics are slow, affecting the electrochemical performance.
By growing nano silver iodide (AgI) on the surface of graphene fiber electrodes, the solid electrolyte nano silver iodide is grafted in situ by using Co60-ray irradiation to improve the ionic conductivity and electrochemical performance of the fiber electrodes at low temperatures.
It significantly improves the electrochemical performance of graphene fiber energy storage devices in low temperature environments, including improving ionic conductivity, accelerating reaction kinetics, and improving cyclic stability and flexibility.
Smart Images

Figure CN119711157A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of manufacturing electrical components, and in particular to a low-temperature resistant graphene fiber energy storage device and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology, the demand for new high-performance materials is growing, especially in the fields of energy, environment, medicine and electronics. Graphene fiber, as a macroscopic one-dimensional material composed of microscopic graphene sheets tightly and orderly arranged, has attracted much attention due to its excellent mechanical strength, electrical conductivity, light weight and efficient thermal conductivity. Graphene fiber not only inherits the excellent properties of graphene, such as ultra-light weight, excellent flexibility and easy functionalization, but also is compatible with traditional cultural technologies, providing new possibilities for the development of wearable electronic devices, flexible energy devices and smart textiles. Graphene capacitors have the characteristics of fast charging and discharging and high energy density, and are suitable for power management systems in electronic products such as smartphones and tablets. As consumers' requirements for the performance of electronic products continue to increase, the application of graphene capacitors in electronic products will become more and more extensive. In the field of transportation, graphene capacitors can be used for starting power supply, braking energy recovery and auxiliary power supply. With the rapid development of the new energy vehicle industry, the application prospects of graphene capacitors in the field of transportation are very broad. However, in low temperature environments below -40℃, supercapacitors still face the problem of being unable to maintain high energy storage characteristics. Maintaining high capacity and fast charge / discharge capabilities at ultra-low temperatures is also a key challenge faced by supercapacitors. The low-temperature-restricted ion-accessible specific surface area (SSA) and slow ion transport kinetics hinder the realization of optimal capacitance and rate performance. Therefore, those skilled in the art are eager to disclose an energy storage device that still has high conductivity and cycle performance in a low-temperature environment. Summary of the invention
[0003] The purpose of the present invention is to provide a low-temperature resistant graphene fiber energy storage device and a preparation method thereof, so as to solve the problem that the existing graphene capacitors cannot maintain high capacity and rate performance in a low-temperature environment.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a low-temperature resistant graphene fiber energy storage device, comprising the following steps:
[0006] 1) Ti 3 AlC 2 Mixing with an etching solution to perform an etching reaction to obtain a MXene solution;
[0007] 2) mixing the MXene solution, the graphene oxide dispersion and the poly (3,4-ethylenedioxythiophene) / polystyrene dispersion to obtain a spinning solution;
[0008] 3) spinning the spinning solution prepared in step 2) to obtain MXene / PEDOT:PSS / GO composite fibers, and then reducing the MXene / PEDOT:PSS / GO composite fibers with a hydroiodic acid solution to obtain MXene / PEDOT:PSS / RGO composite fibers;
[0009] 4) The MXene / PEDOT:PSS / RGO composite fibers were placed in an alcohol solution of silver nitrate for Co 60 -X-ray irradiation to obtain MXene / PEDOT:PSS / RGO composite fibers with AgI grown on the surface;
[0010] 5) The MXene / PEDOT:PSS / RGO composite fiber with AgI grown on the surface prepared in step 4) is made into a capacitor to obtain a graphene fiber energy storage device.
[0011] Preferably, the etching solution in step 1) is prepared by dissolving lithium fluoride in hydrochloric acid;
[0012] The mass volume ratio of lithium fluoride to hydrochloric acid is 3.2-4 g:40 mL;
[0013] The concentration of the hydrochloric acid is 9-12 mol / L.
[0014] Preferably, in step 1) the Ti 3 AlC 2 The mass volume ratio of the etching solution is 1-3g:40mL.
[0015] Preferably, the temperature of the etching reaction in step 1) is 30-40° C., and the etching reaction time is 40-44 hours.
[0016] Preferably, the concentration of MXene in the MXene solution in step 2) is 10 to 20 mg / mL;
[0017] The concentration of the graphene oxide dispersion is 15 to 20 mg / mL;
[0018] The concentration of the poly (3,4-ethylenedioxythiophene) / polystyrene dispersion is 1 to 1.5 wt %.
[0019] Preferably, in step 2), the mass ratio of MXene in the spinning solution, graphene oxide in the spinning solution, and poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate in the spinning solution is 4-6:1.5-2.5:4-6.
[0020] Preferably, the concentration of the hydroiodic acid solution in step 3) is 45-50 wt %;
[0021] The reduction temperature is 20-28° C., and the reduction time is 10-14 hours.
[0022] Preferably, the concentration of silver nitrate in the alcohol solution of silver nitrate in step 4) is 0.03-0.06 mol / L;
[0023] The Co 60 The dose rate of -ray irradiation is 50-70gy / min, and the total irradiation dose is 300kgy.
[0024] The present invention also provides a low-temperature resistant graphene fiber energy storage device prepared by the above preparation method.
[0025] The present invention has at least the following beneficial effects:
[0026] The electrochemical performance of AgI is mainly affected by its crystal form changes. When the temperature is lower than 408K, its stable state is γ-AgI with a cubic structure of sphalerite; when the temperature is between 408K and 419K, it is β-AgI with a wurtzite crystal form; when the temperature is higher than 419K, it is α-AgI with a body-centered cubic structure. Therefore, the present invention uses Co 60 -Ray irradiation in situ grafting of solid electrolyte nano silver iodide on the fiber surface to improve the electrochemical performance of the fiber electrode in a low temperature environment. Nano silver iodide has an ice-like structure, similar to the ice crystal structure, and can act as an ice nucleus to promote better migration and conduction of ions in the electrolyte, thereby improving the ionic conductivity of the fiber electrode at low temperatures and improving the electrochemical performance; nano silver iodide has a small particle size and a large specific surface area, which can provide more active sites for electrode reactions, making the electrode's redox reaction at low temperatures easier, accelerating the reaction kinetics, and improving the electrode's electrochemical performance; nano silver iodide can form a protective film on the surface of the fiber electrode to prevent the electrode material from having side reactions with the electrolyte at low temperatures, while stabilizing the structure of the electrode interface and reducing the interface impedance, thereby improving the low-temperature electrochemical performance of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The data statistics of strain force, fiber diameter, tensile strength at break and conductivity of the RGO fiber (label #1) prepared in comparative example 1, the PEDOT:PSS / RGO composite fiber (label #2) prepared in comparative example 2, the MPG fiber (label #3) prepared in comparative example 3 and the MPG@AgI fiber (label #4) prepared in example 1 are shown;
[0028] Figure 2Cyclic voltammetry curves of the low-temperature resistant graphene fiber energy storage device (MPG-FZ) prepared in Example 1 and the graphene fiber energy storage device (MPG) prepared in Comparative Example 3 at 30° C. and a scan rate of 50 mv / s;
[0029] Figure 3 Cyclic voltammetry curves of the low-temperature resistant graphene fiber energy storage device (MPG-FZ) prepared in Example 1 and the graphene fiber energy storage device (MPG) prepared in Comparative Example 3 at 0°C and a scan rate of 50mv / s;
[0030] Figure 4 Cyclic voltammetry curves of the low-temperature resistant graphene fiber energy storage device (MPG-FZ) prepared in Example 1 and the graphene fiber energy storage device (MPG) prepared in Comparative Example 3 at -20°C and a scan rate of 50mv / s;
[0031] Figure 5 Cyclic voltammetry curves of the low-temperature resistant graphene fiber energy storage device (MPG-FZ) prepared in Example 1 and the graphene fiber energy storage device (MPG) prepared in Comparative Example 3 at -40°C and a scan rate of 50mv / s;
[0032] Figure 6 Cyclic voltammetry curves of the low-temperature resistant graphene fiber energy storage device (MPG-FZ) prepared in Example 1 and the graphene fiber energy storage device (MPG) prepared in Comparative Example 3 at -60°C and a scan rate of 50mv / s;
[0033] Figure 7 This is a constant current charge and discharge (GCD) curve of the low temperature resistant graphene fiber energy storage device prepared in Example 1;
[0034] Figure 8 The AC impedance spectrum of the low-temperature resistant graphene fiber energy storage device prepared in Example 1;
[0035] Fig. 9 The cycle performance curve of the low temperature resistant graphene fiber energy storage device prepared in Example 1 at 30°C;
[0036] Fig.10 The cycle performance curve of the low temperature resistant graphene fiber energy storage device prepared in Example 1 at 0°C;
[0037] Fig.11 The cycle performance curve of the low-temperature resistant graphene fiber energy storage device prepared in Example 1 at -20°C;
[0038] Fig.12The cycle performance curve of the low-temperature resistant graphene fiber energy storage device prepared in Example 1 at -40°C;
[0039] Fig.13 The cyclic voltammetry curves of the low-temperature resistant graphene fiber energy storage device prepared in Example 1 after being bent at different angles at 30°C;
[0040] Fig.14 The cyclic voltammetry curves of the low-temperature resistant graphene fiber energy storage device prepared in Example 1 after being bent at different angles at -40°C;
[0041] Fig.15 The voltage-current curves after connecting different numbers of low-temperature resistant graphene fiber energy storage devices prepared in Example 1 in series;
[0042] Fig.16 The voltage-current curves are obtained after connecting different numbers of low-temperature-resistant graphene fiber energy storage devices prepared in Example 1 in parallel. DETAILED DESCRIPTION
[0043] The present invention provides a method for preparing a low-temperature resistant graphene fiber energy storage device, comprising the following steps:
[0044] 1) Ti 3 AlC 2 Mixing with an etching solution to perform an etching reaction to obtain a MXene solution;
[0045] 2) mixing the MXene solution, the graphene oxide dispersion and the poly (3,4-ethylenedioxythiophene) / polystyrene dispersion to obtain a spinning solution;
[0046] 3) spinning the spinning solution prepared in step 2) to obtain MXene / PEDOT:PSS / GO composite fibers, and then reducing the MXene / PEDOT:PSS / GO composite fibers with a hydroiodic acid solution to obtain MXene / PEDOT:PSS / RGO composite fibers;
[0047] 4) The MXene / PEDOT:PSS / RGO composite fibers were placed in an alcohol solution of silver nitrate for Co 60 -X-ray irradiation to obtain MXene / PEDOT:PSS / RGO composite fibers with AgI grown on the surface;
[0048] 5) The MXene / PEDOT:PSS / RGO composite fiber with AgI grown on the surface prepared in step 4) is made into a capacitor to obtain a graphene fiber energy storage device.
[0049] In the present invention, the etching solution in step 1) is prepared by dissolving lithium fluoride in hydrochloric acid.
[0050] In the present invention, the mass volume ratio of lithium fluoride to hydrochloric acid is 3.2-4 g:40 mL, preferably 3.3-3.9 g:40 mL, more preferably 3.4-3.8 g:40 mL, and more preferably 3.5-3.7 g:40 mL.
[0051] In the present invention, the concentration of the hydrochloric acid is 9 to 12 mol / L, preferably 9.5 to 11.5 mol / L, and more preferably 10 to 11 mol / L.
[0052] In the present invention, the Ti in step 1) 3 AlC 2 The mass volume ratio of the etching solution is 1 to 3 g:40 mL, preferably 1.3 to 2.8 g:40 mL, more preferably 1.5 to 2.5 g:40 mL, more preferably 1.8 to 2.2 g, and even more preferably 2 g.
[0053] In the present invention, the temperature of the etching reaction in step 1) is 30-40°C, preferably 32-38°C, further preferably 34-36°C, and more preferably 35°C; the etching reaction time is 40-44h, preferably 40.5-43.5h, further preferably 41-43h, and more preferably 41.5-42h.
[0054] In the present invention, after the etching reaction in step 1) is completed, the step of separating and purifying the reaction product is also included, specifically, washing the product with deionized water and then centrifuging it with a centrifuge, and repeating the washing until the pH value of the product solution is 5-7; after the washing is completed, the volume of the bottom product swells and becomes sticky, and it is placed in an ultrasonic cleaner, and ultrasonically treated at 10-15°C and 32kHz for 1h under the protection of an inert gas to promote the separation of MXene sheets; after the ultrasonic treatment, the mixed solution is centrifuged at a speed of 3500rpm for 60min, and the supernatant is the MXene solution, which can be directly used to prepare the spinning solution.
[0055] In the present invention, the concentration of MXene in the MXene solution in step 2) is 10 to 20 mg / mL, preferably 12 to 18 mg / mL, more preferably 14 to 16 mg / mL, and more preferably 15 mg / mL.
[0056] In the present invention, the concentration of the graphene oxide dispersion in step 2) is 15 to 20 mg / mL, preferably 16 to 19 mg / mL, and more preferably 17 to 18 mg / mL.
[0057] In the present invention, the concentration of the poly (3,4-ethylenedioxythiophene) / polystyrene dispersion in step 2) is 1 to 1.5 wt %, preferably 1.1 to 1.4 wt %, and more preferably 1.2 to 1.3 wt %.
[0058] In the present invention, the mass ratio of MXene in the spinning solution, graphene oxide in the spinning solution and poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate in the spinning solution in step 2) is 4-6: 1.5-2.5: 4-6, preferably 4.3-5.8: 1.7-2.3: 4.3-5.8, further preferably 4.5-5.5: 1.9-2.1: 4.5-5.5, and more preferably 4.8-5: 2: 4.8-5.
[0059] In the present invention, the spinning method in step 3) is to fix a No. 18 stainless steel needle with an inner diameter of 0.84 mm on a 10 ml screw-mouth syringe, load the spinning solution therein, and then install the syringe on a syringe pump (LEADFLUIDTYD01), and extrude the spinning solution at a speed of 0.16 to 0.26 mL / min, preferably 0.18 to 0.24 mL / min, and more preferably 0.2 to 0.22 mL / min; the spun fiber is directly extruded into acetic acid.
[0060] In the present invention, the spinning method in step 3) is to directly immerse the extruded spinning in acetic acid, and the temperature of immersing the MXene / PEDOT:PSS / GO composite fiber in acetic acid is 20-26°C, preferably 21-25°C, more preferably 22-24°C, and more preferably 23°C; the time is 10-25min, preferably 13-22min, more preferably 15-20min, and more preferably 16-18min.
[0061] In the present invention, the concentration of the hydroiodic acid solution is 45 to 50 wt %, preferably 46 to 49 wt %, and more preferably 47 to 48 wt %.
[0062] In the present invention, the reduction temperature is 20-28°C, and can be 20°C, 22°C, 24°C, 25°C, 26°C, or 28°C; the reduction time is 10-14h, preferably 11-13h, and more preferably 12h.
[0063] In the present invention, after the reduction reaction in step 3) is completed, the MXene / PEDOT:PSS / RGO composite fiber is further washed and dried, specifically, first washed with ethanol for 4 to 7 times, and then washed with deionized water for 3 to 5 times; the drying temperature is 20 to 30°C, and the drying time is 20 to 28 hours.
[0064] In the present invention, the concentration of silver nitrate in the alcoholic silver nitrate solution in step 4) is 0.03-0.06 mol / L, preferably 0.035-0.055 mol / L, more preferably 0.04-0.05 mol / L, and more preferably 0.045 mol / L.
[0065] In the present invention, the Co 60 The dose rate of -ray irradiation is 50 to 70 gy / min, preferably 55 to 65 gy / min, more preferably 58 to 62 gy / min, and more preferably 60 gy / min; the total irradiation dose is 300 kgy.
[0066] In the present invention, the preparation method of the low temperature resistant graphene fiber energy storage device in step 5) is:
[0067] Copper foil was wrapped around both ends of the polyester resin substrate, and the head end of a MXene / PEDOT:PSS / RGO composite fiber with AgI grown on the surface was fixed to the copper foil at one end with silver paste, and then the head end of another electrode parallel to the first one was also fixed to the copper foil at the other end of the substrate. PVA / LiCl gel electrolyte was dropped on the opposite parts of the two electrodes and allowed to stand and solidify at room temperature for 24 hours to obtain a low-temperature resistant graphene fiber energy storage device.
[0068] The preparation method of the PVA / LiCl gel electrolyte is as follows: lithium chloride, deionized water and polyvinyl alcohol are mixed and stirred at 90° C. for 1 hour, and then placed at room temperature for 48 hours to obtain the PVA / LiCl gel electrolyte.
[0069] The present invention also provides a low-temperature resistant graphene fiber energy storage device prepared by the above preparation method.
[0070] The low-temperature resistant graphene fiber energy storage device can be used as a supercapacitor.
[0071] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0072] Example 1
[0073] (1) 3.2 g of lithium fluoride powder was dissolved in 40 mL of 9 mol / L hydrochloric acid solution to obtain an etching solution, and then 2 g of Ti 3 AlC 2The powder was slowly added to the etching solution. After etching at 35°C for 40 hours, deionized water was added to the system for dilution. The system was then centrifuged at 3500 rpm for 5 minutes. After removing the supernatant containing a large amount of acid, deionized water was added again for washing and centrifugation. After repeating 12 times, the pH value of the supernatant was 6, and the cleaning was completed. After cleaning, the product expanded and became sticky. Deionized water was added and placed in an ultrasonic cleaner. Under the protection of inert gas nitrogen, ultrasound was performed at 10°C and 32kHz for 1 hour to promote the separation of MXene sheets. After the ultrasound was completed, the solution was divided into centrifuge tubes and centrifuged at 3500 rpm for 60 minutes. The bottom liquid was removed, and the upper clear liquid obtained was the MXene solution with a concentration of 10 mg·mL -1 .
[0074] (2) Dispersing graphene oxide (GO) powder in deionized water, stirring until there are no obvious lumps in the solution, and ultrasonically dispersing in an ice-water bath for 2 h to obtain a GO aqueous dispersion with a concentration of 18 mg / mL; mixing the MXene solution and GO aqueous dispersion prepared in step (1) with a PEDOT:PSS solution (poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate, 1 wt%, Heraeus CLEVIOS PH1000, Germany) to obtain a MXene / PEDOT:PSS / GO spinning solution, wherein the mass ratio of MXene, GO, and PEDOT:PSS in the spinning solution is 5:2:5.
[0075] (3) A No. 18 stainless steel needle with an inner diameter of 0.84 mm was fixed on a 10 ml screw-mouth syringe and the MXene / PEDOT:PSS / GO spinning solution was loaded into it. After the syringe was installed on the syringe pump (LEADFLUIDTYD01), the spinning solution was extruded into an icy acetic acid bath at a rate of 0.2 mL / min and soaked for 15 min. The fiber was then reduced with 47 wt% hydroiodic acid at room temperature for 12 h, washed with ethanol 6 times, washed with deionized water 4 times, collected on a polytetrafluoroethylene cylinder, and dried at room temperature for 24 h to obtain a MXene / PEDOT:PSS / RGO composite fiber in which the mass fraction of MXene was 42%.
[0076] (4) The MXene / PEDOT:PSS / RGO composite fibers after hydroiodic acid reduction were placed in a 0.05 mol silver nitrate / ethanol solution and heated to 40°C with a Co2 / MgCl2 solution at a dose rate of 70 gy / min. 60 -ray irradiation, the total irradiation dose is 300kgy, and the MXene / PEDOT:PSS / RGO composite fiber with solid electrolyte AgI grown on the surface is obtained. The fiber is collected on a PTFE cylinder and dried at room temperature for 24h, which is recorded as MPG@AgI fiber.
[0077] (5) 7.5 g of lithium chloride and 50 mL of deionized water were mixed and magnetically stirred for 10 min. Then, 5 g of polyvinyl alcohol was added, and the mixture was stirred at 90 °C for 1 h and allowed to stand at room temperature for 48 h to obtain a PVA / LiCl gel electrolyte.
[0078] Copper foil was wrapped around both ends of the polyester resin substrate, and the head of an MPG@AgI fiber electrode was fixed to the copper foil at one end with silver paste, and then the head of another electrode parallel to the first one was also fixed to the copper foil at the other end of the substrate. PVA / LiCl gel electrolyte was dropped on the opposite parts of the two electrodes and allowed to stand and solidify at room temperature for 24 hours to obtain a low-temperature resistant graphene fiber energy storage device.
[0079] Example 2
[0080] (1) 3.8 g of lithium fluoride powder was dissolved in 40 mL of 9 mol / L hydrochloric acid solution to obtain an etching solution, and then 3 g of Ti 3 AlC 2 The powder was slowly added to the etching solution. After etching at 30°C for 44 hours, deionized water was added to the system for dilution. The system was then centrifuged at 3500 rpm for 5 minutes. After removing the supernatant containing a large amount of acid, deionized water was added again for washing and centrifugation. After repeating 12 times, the pH value of the supernatant was 6, and the cleaning was completed. After cleaning, the product expanded and became sticky. Deionized water was added and placed in an ultrasonic cleaner. Under the protection of inert gas nitrogen, ultrasound was performed at 10°C and 32kHz for 1 hour to promote the separation of MXene sheets. After the ultrasound was completed, the solution was divided into centrifuge tubes and centrifuged at 3500 rpm for 60 minutes. The bottom liquid was removed, and the supernatant obtained was the MXene solution with a concentration of 12 mg·mL -1 .
[0081] (2) Dispersing graphene oxide (GO) powder in deionized water, stirring until there are no obvious lumps in the solution, and ultrasonically dispersing in an ice-water bath for 2 hours to obtain a GO aqueous dispersion with a concentration of 18 mg / mL; mixing the MXene solution and GO aqueous dispersion prepared in step (1) with a PEDOT:PSS solution (poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate, 1 wt%) to obtain a MXene / PEDOT:PSS / GO spinning solution, wherein the mass ratio of MXene, GO, and PEDOT:PSS in the spinning solution is 5:1.8:4.5.
[0082] (3) A No. 18 stainless steel needle with an inner diameter of 0.84 mm was fixed on a 10 ml screw-mouth syringe and the MXene / PEDOT:PSS / GO spinning solution was loaded into it. After the syringe was installed on the syringe pump (LEADFLUIDTYD01), the spinning solution was extruded into an icy acetic acid bath at a rate of 0.18 mL / min and soaked for 15 min. The fiber was then reduced with 47 wt% hydroiodic acid at room temperature for 10 h, washed with ethanol 6 times, washed with deionized water 4 times, collected on a polytetrafluoroethylene cylinder, and dried at room temperature for 24 h to obtain a MXene / PEDOT:PSS / RGO composite fiber in which the mass fraction of MXene was 44%.
[0083] (4) The MXene / PEDOT:PSS / RGO composite fiber after hydroiodic acid reduction was placed in a 0.04 mol silver nitrate / ethanol solution and irradiated with Co60-rays at a dose rate of 70 gy / min. The total irradiation dose was 300 kgy to obtain a MXene / PEDOT:PSS / RGO composite fiber with solid electrolyte AgI grown on the surface. The fiber was collected on a PTFE cylinder and dried at room temperature for 24 h, which was recorded as MPG@AgI fiber.
[0084] (5) 7.5 g of lithium chloride and 50 mL of deionized water were mixed and magnetically stirred for 10 min. Then, 5 g of polyvinyl alcohol was added, and the mixture was stirred at 90 °C for 1 h and allowed to stand at room temperature for 48 h to obtain a PVA / LiCl gel electrolyte.
[0085] Copper foil was wrapped around both ends of the polyester resin substrate, and the head of an MPG@AgI fiber electrode was fixed to the copper foil at one end with silver paste, and then the head of another electrode parallel to the first one was also fixed to the copper foil at the other end of the substrate. PVA / LiCl gel electrolyte was dropped on the opposite parts of the two electrodes and allowed to stand and solidify at room temperature for 24 hours to obtain a low-temperature resistant graphene fiber energy storage device.
[0086] Example 3
[0087] (1) 3.2 g of lithium fluoride powder was dissolved in 40 mL of 9 mol / L hydrochloric acid solution to obtain an etching solution, and then 2 g of Ti 3 AlC 2The powder was slowly added to the etching solution. After etching at 40°C for 40 hours, deionized water was added to the system for dilution. The system was then centrifuged at 3500 rpm for 5 minutes. After removing the supernatant containing a large amount of acid, deionized water was added again for washing and centrifugation. After repeating 12 times, the pH value of the supernatant was 6, and the cleaning was completed. After cleaning, the product expanded and became sticky. Deionized water was added and placed in an ultrasonic cleaner. Under the protection of inert gas nitrogen, ultrasound was performed at 10°C and 32kHz for 1 hour to promote the separation of MXene sheets. After the ultrasound was completed, the solution was divided into centrifuge tubes and centrifuged at 3500 rpm for 60 minutes. The bottom liquid was removed, and the supernatant obtained was the MXene solution with a concentration of 10 mg·mL -1 .
[0088] (2) Dispersing graphene oxide (GO) powder in deionized water, stirring until there are no obvious lumps in the solution, and ultrasonically dispersing in an ice-water bath for 2 hours to obtain a GO aqueous dispersion with a concentration of 18 mg / mL; mixing the MXene solution and GO aqueous dispersion prepared in step (1) with a PEDOT:PSS solution (poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate, 1 wt%) to obtain a MXene / PEDOT:PSS / GO spinning solution, wherein the mass ratio of MXene, GO, and PEDOT:PSS in the spinning solution is 5:2:5.
[0089] (3) Fix a No. 18 stainless steel needle with an inner diameter of 0.84 mm on a 10 ml screw-mouth syringe and load the MXene / PEDOT:PSS / GO spinning solution into it. After installing the syringe on the syringe pump (LEADFLUIDTYD01), extrude the spinning solution into an icy acetic acid bath at a rate of 0.21 mL / min and soak for 15 min. Then reduce the fiber with 45 wt% hydroiodic acid at room temperature for 14 h, wash it with ethanol 6 times, wash it with deionized water 4 times, collect it on a polytetrafluoroethylene cylinder, and dry it at room temperature for 24 h to obtain MXene / PEDOT:PSS / RGO composite fibers, in which the mass fraction of MXene is 42%.
[0090] (4) The MXene / PEDOT:PSS / RGO composite fiber after hydroiodic acid reduction was placed in a 0.05 mol silver nitrate / ethanol solution and irradiated with Co60-rays at a dose rate of 70 gy / min. The total irradiation dose was 300 kgy to obtain a MXene / PEDOT:PSS / RGO composite fiber with solid electrolyte AgI grown on the surface. The fiber was collected on a PTFE cylinder and dried at room temperature for 24 h, which was recorded as MPG@AgI fiber.
[0091] (5) 7.5 g of lithium chloride and 50 mL of deionized water were mixed and magnetically stirred for 10 min. Then, 5 g of polyvinyl alcohol was added, and the mixture was stirred at 90 °C for 1 h and allowed to stand at room temperature for 48 h to obtain a PVA / LiCl gel electrolyte.
[0092] Copper foil was wrapped around both ends of the polyester resin substrate, and the head of an MPG@AgI fiber electrode was fixed to the copper foil at one end with silver paste, and then the head of another electrode parallel to the first one was also fixed to the copper foil at the other end of the substrate. PVA / LiCl gel electrolyte was dropped on the opposite parts of the two electrodes and allowed to stand and solidify at room temperature for 24 hours to obtain a low-temperature resistant graphene fiber energy storage device.
[0093] Example 4
[0094] (1) Dissolve 3.5 g of lithium fluoride powder in 40 mL of 12 mol / L hydrochloric acid solution to obtain an etching solution, and then 2 g of Ti 3 AlC 2 The powder was slowly added to the etching solution. After etching at 38°C for 42 hours, deionized water was added to the system for dilution. The system was then centrifuged at 3500 rpm for 5 minutes. After removing the supernatant containing a large amount of acid, deionized water was added again for washing and centrifugation. After repeating 13 times, the pH value of the supernatant was 6, and the cleaning was completed. After cleaning, the product expanded and became sticky. Deionized water was added and placed in an ultrasonic cleaner. Under the protection of inert gas nitrogen, ultrasound was performed at 10°C and 32kHz for 1 hour to promote the separation of MXene sheets. After the ultrasound was completed, the solution was divided into centrifuge tubes and centrifuged at 3500 rpm for 60 minutes. The bottom liquid was removed, and the supernatant obtained was the MXene solution with a concentration of 15 mg·mL -1 .
[0095] (2) Dispersing graphene oxide (GO) powder in deionized water, stirring until there are no obvious lumps in the solution, and ultrasonically dispersing in an ice-water bath for 2 hours to obtain a GO aqueous dispersion with a concentration of 20 mg / mL; mixing the MXene solution and GO aqueous dispersion prepared in step (1) with a PEDOT:PSS solution (poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate, 10 wt%) to obtain a MXene / PEDOT:PSS / GO spinning solution, wherein the mass ratio of MXene, GO, and PEDOT:PSS in the spinning solution is 5:2:5.
[0096] (3) A No. 18 stainless steel needle with an inner diameter of 0.84 mm was fixed on a 10 ml screw-mouth syringe and the MXene / PEDOT:PSS / GO spinning solution was loaded into it. After the syringe was installed on the syringe pump (LEADFLUIDTYD01), the spinning solution was extruded into an icy acetic acid bath at a rate of 0.24 mL / min and soaked for 20 min. The fiber was then reduced with 50 wt% hydroiodic acid at room temperature for 10 h, washed 6 times with ethanol, 4 times with deionized water, collected on a polytetrafluoroethylene cylinder, and dried at room temperature for 24 h to obtain a MXene / PEDOT:PSS / RGO composite fiber in which the mass fraction of MXene was 42%.
[0097] (4) The MXene / PEDOT:PSS / RGO composite fiber after hydroiodic acid reduction was placed in a 0.05 mol silver nitrate / ethanol solution and irradiated with Co60-rays at a dose rate of 70 gy / min. The total irradiation dose was 300 kgy to obtain a MXene / PEDOT:PSS / RGO composite fiber with solid electrolyte AgI grown on the surface. The fiber was collected on a PTFE cylinder and dried at room temperature for 24 h, which was recorded as MPG@AgI fiber.
[0098] (5) 7.5 g of lithium chloride and 50 mL of deionized water were mixed and magnetically stirred for 10 min. Then, 5 g of polyvinyl alcohol was added, and the mixture was stirred at 90 °C for 1 h and allowed to stand at room temperature for 48 h to obtain a PVA / LiCl gel electrolyte.
[0099] Copper foil was wrapped around both ends of the polyester resin substrate, and the head of an MPG@AgI fiber electrode was fixed to the copper foil at one end with silver paste, and then the head of another electrode parallel to the first one was also fixed to the copper foil at the other end of the substrate. PVA / LiCl gel electrolyte was dropped on the opposite parts of the two electrodes and allowed to stand and solidify at room temperature for 24 hours to obtain a low-temperature resistant graphene fiber energy storage device.
[0100] Comparative Example 1
[0101] (1) Preparation of GO spinning solution: Graphene oxide powder (the powder was purchased from Shenzhen Turing Evolution Technology Co., Ltd.) was dispersed in deionized water and stirred until there were no obvious lumps in the solution. The solution was magnetically stirred until the magnet could not rotate, and ultrasonically dispersed in an ice-water bath for 2 h to obtain an 18 mg / mL GO aqueous dispersion.
[0102] (2) A No. 18 stainless steel needle with an inner diameter of 0.84 mm was fixed on a 10 ml screw-mouth syringe and the GO spinning solution was loaded into it. After the syringe was installed on a syringe pump (LEADFLUIDTYD01), the spinning solution was extruded into an icy acetic acid bath at a rate of 0.2 mL / min and soaked for 15 min. The fiber was then reduced with 47 wt% hydroiodic acid at room temperature for 12 h, washed with ethanol 6 times, washed with deionized water 4 times, collected on a polytetrafluoroethylene cylinder, and dried at room temperature for 24 h to obtain RGO fiber.
[0103] (3) 7.5 g of lithium chloride and 50 mL of deionized water were mixed, and the mixture was stirred magnetically for 10 min. Then, 5 g of polyvinyl alcohol was added, and the mixture was stirred at 90 °C for 1 h. The mixture was allowed to stand at room temperature for 48 h to obtain a PVA / LiCl gel electrolyte.
[0104] Copper foil was wrapped around both ends of the polyester resin substrate, and the head of an MPG@AgI fiber electrode was fixed to the copper foil at one end with silver paste, and then the head of another electrode parallel to the first one was also fixed to the copper foil at the other end of the substrate. PVA / LiCl gel electrolyte was dropped on the opposite parts of the two electrodes and cured at room temperature for 24 hours to obtain a graphene fiber energy storage device.
[0105] Comparative Example 2
[0106] (1) Graphene oxide (GO) powder was dispersed in deionized water, stirred until there were no obvious lumps in the solution, and ultrasonically dispersed in an ice-water bath for 2 h to obtain a GO aqueous dispersion with a concentration of 18 mg / mL; the GO aqueous dispersion was mixed with a PEDOT:PSS solution (poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate, 1 wt%) to obtain a PEDOT:PSS / GO spinning solution, in which the mass ratio of GO to PEDOT:PSS in the spinning solution was 2:5.
[0107] (2) A No. 18 stainless steel needle with an inner diameter of 0.84 mm was fixed on a 10 ml screw-mouth syringe and the PEDOT:PSS / GO spinning solution was loaded into it. After the syringe was installed on a syringe pump (LEADFLUIDTYD01), the spinning solution was extruded into an icy acetic acid bath at a rate of 0.2 mL / min and soaked for 15 min. The fiber was then reduced with 47 wt% hydroiodic acid at room temperature for 12 h, washed with ethanol 6 times, washed with deionized water 4 times, collected on a polytetrafluoroethylene cylinder, and dried at room temperature for 24 h to obtain PEDOT:PSS / RGO composite fibers.
[0108] (3) 7.5 g of lithium chloride and 50 mL of deionized water were mixed, and the mixture was stirred magnetically for 10 min. Then, 5 g of polyvinyl alcohol was added, and the mixture was stirred at 90 °C for 1 h. The mixture was allowed to stand at room temperature for 48 h to obtain a PVA / LiCl gel electrolyte.
[0109] Copper foil was wrapped around both ends of the polyester resin substrate, and the head of a PEDOT:PSS / RGO composite fiber electrode was fixed to the copper foil at one end with silver paste, and then the head of another electrode parallel to the first one was also fixed to the copper foil at the other end of the substrate. PVA / LiCl gel electrolyte was dropped on the opposite parts of the two electrodes and allowed to stand and solidify at room temperature for 24 hours to obtain a graphene fiber energy storage device.
[0110] Comparative Example 3
[0111] (1) 3.2 g of lithium fluoride powder was dissolved in 40 mL of 9 mol / L hydrochloric acid solution to obtain an etching solution, and then 2 g of Ti 3 AlC 2 The powder was slowly added to the etching solution. After etching at 35°C for 40 hours, deionized water was added to the system for dilution. The system was then centrifuged at 3500 rpm for 5 minutes. After removing the supernatant containing a large amount of acid, deionized water was added again for washing and centrifugation. After repeating 12 times, the pH value of the supernatant was 6, and the cleaning was completed. After cleaning, the product expanded and became sticky. Deionized water was added and placed in an ultrasonic cleaner. Under the protection of inert gas nitrogen, ultrasound was performed at 10°C and 32kHz for 1 hour to promote the separation of MXene sheets. After the ultrasound was completed, the solution was divided into centrifuge tubes and centrifuged at 3500 rpm for 60 minutes. The bottom liquid was removed, and the upper clear liquid obtained was the MXene solution with a concentration of 10 mg·mL -1 .
[0112] (2) Dispersing graphene oxide (GO) powder in deionized water, stirring until there are no obvious lumps in the solution, and ultrasonically dispersing in an ice-water bath for 2 hours to obtain a GO aqueous dispersion with a concentration of 18 mg / mL; mixing the MXene solution and GO aqueous dispersion prepared in step (1) with a PEDOT:PSS solution (poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate, 1 wt%) to obtain a MXene / PEDOT:PSS / GO spinning solution, wherein the mass ratio of MXene, GO, and PEDOT:PSS in the spinning solution is 5:2:5.
[0113] (3) A No. 18 stainless steel needle with an inner diameter of 0.84 mm was fixed on a 10 ml screw-mouth syringe and the MXene / PEDOT:PSS / GO spinning solution was loaded into it. After the syringe was installed on the syringe pump (LEADFLUIDTYD01), the spinning solution was extruded into an icy acetic acid bath at a rate of 0.2 mL / min and soaked for 15 min. The fiber was then reduced with 47 wt% hydroiodic acid at room temperature for 12 h, washed with ethanol 6 times, washed with deionized water 4 times, collected on a polytetrafluoroethylene cylinder, and dried at room temperature for 24 h to obtain MXene / PEDOT:PSS / RGO composite fibers, recorded as MPG fibers, in which the mass fraction of MXene was 42%.
[0114] (4) 7.5 g of lithium chloride and 50 mL of deionized water were mixed, and the mixture was magnetically stirred for 10 min. Then, 5 g of polyvinyl alcohol was added, and the mixture was stirred at 90 °C for 1 h. The mixture was allowed to stand at room temperature for 48 h to obtain a PVA / LiCl gel electrolyte.
[0115] Copper foil was wrapped around both ends of the polyester resin substrate, and the head of an MPG fiber electrode was fixed to the copper foil at one end with silver paste, and then the head of another electrode parallel to the first one was also fixed to the copper foil at the other end of the substrate. PVA / LiCl gel electrolyte was dropped on the opposite parts of the two electrodes and allowed to stand and solidify at room temperature for 24 hours to obtain a graphene fiber energy storage device.
[0116] The strain, fiber diameter, tensile strength and conductivity of the RGO fiber (label #1) prepared in Comparative Example 1, the PEDOT:PSS / RGO composite fiber (label #2) prepared in Comparative Example 2, the MPG fiber (label #3) prepared in Comparative Example 3 and the MPG@AgI fiber (label #4) prepared in Example 1 were tested. The test results are shown in Figure 2. Figure 1 As shown in the figure, the tensile breaking strengths of RGO fiber, PEDOT:PSS / RGO composite fiber, MPG fiber and MPG@AgI fiber are 46MPa, 55MPa, 175MPa and 180MPa, respectively; the electrical conductivity of MPG@AgI fiber is 396S / cm, which is 5 times that of RGO fiber, 3.7 times that of PEDOT:PSS / RGO composite fiber and 1.3 times that of MPG fiber.
[0117] The test method for the above fiber diameter is to calculate the fiber diameter using a polarizing microscope and ImageJ software. The test method for conductivity is to use Guangzhou Four Probe Technology RTS-9 Four Probe Conductivity Meter to test the fiber conductivity, measure 3 to 5 points for each sample, and take the average value. The test method for tensile breaking strength is to use INSTRON5969 Electronic Universal Material Strength Tester to test the fiber mechanical properties, with a clamping distance of 20 mm, a tensile rate of 5 mm / min, and measure 3 to 5 times for each sample, and take the average value.
[0118] The electrochemical parameters of the MPG-AgI fibers and MPG fibers prepared in Example 1 and Comparative Example 3 are shown in Table 1:
[0119] Table 1 Electrochemical parameters of MPG-AgI fibers and MPG fibers prepared in Example 1 and Comparative Example 3
[0120]
[0121]
[0122] The Cv, Pv and Ev of the MPG fiber material at -40°C and -60°C cannot be measured, which further illustrates that the MPG-AgI fiber prepared by the present invention also has good performance in a low temperature environment.
[0123] The electrochemical performance of the low-temperature resistant graphene fiber energy storage device prepared in Example 1 was tested by a two-electrode method using a CS electrochemical workstation of Wuhan Koster Instruments:
[0124] 1. The energy storage device (MPG) without solid electrolyte AgI prepared in Comparative Example 3 and the energy storage device (MPG-FZ) loaded with solid electrolyte AgI prepared in Example 1 were subjected to CV test at a scan rate of 50 mv / s at 30°C, 0°C, -20°C, -40°C, and -60°C. The cyclic voltammetry (CV) curves are shown in FIG. Figures 2 to 6 As shown, in contrast, the electrochemical performance of electrodes loaded with solid electrolytes decreases more slowly at low temperatures.
[0125] 2. Test the low-temperature resistant graphene fiber energy storage device prepared in Example 1 at a current density of 0.11.0Acm -3 The constant current charge-discharge (GCD) curve is as follows: Figure 7 As shown, at a current density of 0.1 A cm -3When the GCD curves of the composite fiber electrodes are approximately symmetrical isosceles triangles, indicating that they have good charge and discharge capabilities. Among them, the longest discharge time is at room temperature (30°C), indicating that it has the best electrochemical performance. And as the temperature decreases, the discharge time gradually decreases. This may be because the low temperature environment limits the ion transport in the electrolyte, affecting the normal ion embedding and extraction process, and the reaction kinetics at the electrode / electrolyte interface may slow down, resulting in a decrease in the charge and discharge efficiency of the capacitor.
[0126] 3. At frequency 0.01~10 5 The AC impedance spectrum of the low-temperature resistant graphene fiber energy storage device prepared in Example 1 was tested under the condition of an AC amplitude of 10 mV. Figure 8 As shown, from Figure 8 It can be seen from the figure that the curve is composed of a semicircular arc and an inclined straight line. The intersection of the arc and the horizontal axis is the internal resistance of the electrode. It can be seen from the figure that as the temperature decreases, the internal resistance of the electrode increases and the performance decays.
[0127] Figures 9 to 12 The cycle performance curves of the low temperature resistant graphene fiber energy storage device prepared in Example 1 at 30°C, 0°C, -20°C and -40°C are shown in sequence. Figures 9 to 12 It can be seen that the energy storage device has good cycling stability over 2000 cycles. Even when cycled at -20°C and -40°C, the energy storage device based on MPG@AgI fibers can still maintain 79.1% and 75.9% of the specific capacitance, indicating excellent cycling stability at low temperatures.
[0128] The fiber capacitor prepared in Example 1 was bent at 30°C and -40°C, and its CV curve remained good after cycling at different bending angles from 0° to 180°. Fig.13 and Fig.14 As shown, it exhibits excellent flexibility over a wide operating temperature range.
[0129] In order to verify the performance of MPG@AgI fiber supercapacitors under various voltage and / or power requirements, multiple low-temperature resistant graphene fiber energy storage devices prepared in Example 1 were assembled in series or in parallel to increase the output current or output voltage. The volt-ampere curves of 1 capacitor, 2 capacitors in series, or 3 capacitors in series are shown in Figure 2. Fig.15 As shown in the figure, the potential window of two low-temperature resistant graphene fiber energy storage devices assembled in series reached 4V, and the potential window of three low-temperature resistant graphene fiber energy storage devices assembled in series reached 6V, which is comparable to commercial organic lithium-ion thin film batteries. The voltage of fiber supercapacitors in series devices is positively correlated with their number. The volt-ampere curves of 1 capacitor, 2 capacitors in parallel, or 3 capacitors in parallel are shown in Figure 1. Fig.16 As shown in the figure, the current intensity of two low-temperature resistant graphene fiber energy storage devices assembled in parallel is twice that of one device, and the current intensity of three low-temperature resistant graphene fiber energy storage devices assembled in parallel is three times that of one device. The current intensity of fiber supercapacitors in parallel devices is positively correlated with their number. This shows that a certain number of fiber supercapacitors connected in series or in parallel can meet the current and voltage required to power external devices.
[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a low-temperature resistant graphene fiber energy storage device, characterized in that: The following steps are involved: 1) Mix Ti3AlC2 with an etching solution to perform an etching reaction to obtain a MXene solution; 2) mixing the MXene solution, the graphene oxide dispersion and the poly (3,4-ethylenedioxythiophene) / polystyrene dispersion to obtain a spinning solution; 3) spinning the spinning solution prepared in step 2) to obtain MXene / PEDOT:PSS / GO composite fibers, and then reducing the MXene / PEDOT:PSS / GO composite fibers with a hydroiodic acid solution to obtain MXene / PEDOT:PSS / RGO composite fibers; 4) The MXene / PEDOT:PSS / RGO composite fibers were placed in an alcohol solution of silver nitrate for Co 60 -X-ray irradiation to obtain MXene / PEDOT:PSS / RGO composite fibers with AgI grown on the surface; 5) The MXene / PEDOT:PSS / RGO composite fiber with AgI grown on the surface prepared in step 4) is made into a capacitor to obtain a graphene fiber energy storage device.
2. The method for preparing a low-temperature resistant graphene fiber energy storage device according to claim 1, characterized in that: The etching solution in step 1) is prepared by dissolving lithium fluoride in hydrochloric acid; The mass volume ratio of lithium fluoride to hydrochloric acid is 3.2-4 g:40 mL; The concentration of the hydrochloric acid is 9-12 mol / L.
3. The method for preparing a low-temperature resistant graphene fiber energy storage device according to claim 2, characterized in that: The mass volume ratio of Ti3AlC2 to etching solution in step 1) is 1-3 g:40 mL.
4. A method for preparing a low-temperature resistant graphene fiber energy storage device according to any one of claims 1 to 3, characterized in that: The temperature of the etching reaction in step 1) is 30-40° C., and the time of the etching reaction is 40-44 hours.
5. The method for preparing a low-temperature resistant graphene fiber energy storage device according to claim 4, characterized in that: The concentration of MXene in the MXene solution in step 2) is 10 to 20 mg / mL; The concentration of the graphene oxide dispersion is 15 to 20 mg / mL; The concentration of the poly (3,4-ethylenedioxythiophene) / polystyrene dispersion is 1 to 1.5 wt %.
6. The method for preparing a low-temperature resistant graphene fiber energy storage device according to claim 5, characterized in that: In step 2), the mass ratio of MXene in the spinning solution, graphene oxide in the spinning solution and poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate in the spinning solution is 4-6:1.5-2.5:4-6.
7. A method for preparing a low-temperature resistant graphene fiber energy storage device according to claim 5 or 6, characterized in that: The concentration of the hydroiodic acid solution in step 3) is 45-50 wt %; The reduction temperature is 20-28° C., and the reduction time is 10-14 hours.
8. The method for preparing a low-temperature resistant graphene fiber energy storage device according to claim 7, characterized in that: The concentration of silver nitrate in the alcohol solution of silver nitrate in step 4) is 0.03-0.06 mol / L; The Co 60 The dose rate of -ray irradiation is 50-70gy / min, and the total irradiation dose is 300kgy.
9. A low-temperature resistant graphene fiber energy storage device prepared by the method for preparing a low-temperature resistant graphene fiber energy storage device according to any one of claims 1 to 8.